La transformation de l’ancien centre de détention secrète de Derb Moulay Cherif en musée des « années de plomb » (Casablanca, Maroc) - Anissa Habane (L’Année du Maghreb)
In Morocco, during the "Years of Lead" (1956-1999), a period of intense repression by the monarchy power against any political or social opposition. The country was home to several secret detention centers. Among these was the former Derb Moulay Cherif police station in Casablanca, which operated from 1959 to 1991. For several decades, this secret site, the centerpiece of the repressive system, held, tortured and killed political activists, union members and student activists, as well as random individuals. After the death of King Hassan II in 1999, an emerging body of prison literature in French and Arabic made it possible to expose and inform about the conditions of detention in these secret detention centers. On his arrival to the throne in 1999, the new sovereign Mohammed VI set up two institutions as a response to the mobilization of victims’ and human rights groups. The first one, which is the Commission indépendante d’arbitrage, was set up in 1999 to identify and compensate victims of enforced disappearance and arbitrary detention. Then came the Instance équité et réconciliation (IER), tasked to investigate the truth about human rights violations committed against opponents over a limited period between 1956 and 1999, with the aim of compensating victims, analyzing the institutional causes of human rights violations and proposing reforms to prevent their recurrence. This context of national reconciliation has allowed commemorations in the public arena, previously prohibited. In March 2000, the Forum Vérité Justice (FVJ), bringing together various groups of victims of the repression, organized a rally of almost 1,500 people in front of the former secret detention center of Derb Moulay Cherif (CDS-DMC) to demand its transformation into a museum, thus initiating the process of patrimonialization. In the years that followed, the process of patrimonialization continued from the top down, through the mobilization of public institutions, politicians, experts, associations and artists. Based on an exploratory field study, this article analyzes the process of patrimonialization of the former secret detention center of Derb Moulay Cherif, which for over two decades has mobilized a number of non-profit and institutional actors committed to its preservation and transmission. In the year 2023, where does the patrimonialization process stand? Drawing on the accounts of detainees during the "Years of Lead", scientific papers, written documents and recordings of conferences related to the issue at stake, as well as field observations and several semi-guided interviews conducted in 2023, I will reflect on three different temporalities. The first concerns the establishment of former secret detention centers in the post-independent Moroccan kingdom, enabling us to grasp this painful, shameful and dark period in the country’s history. The second looks back at the temporality of the mobilization. The absence of a possible investment inside the former CDS-DMC, the actions were carried out exclusively in the public space, and in an ephemeral and modest way. The third is blocked by the inability to make use of the building itself has prevented it from being turned into a museum for the time being, to preserve memory and educate future generations. The development of the CDS-DMC remains an important memorial issue, given the lack of interest shown by the authorities and those in power. Furthermore, as the mobilization of former political prisoners in the 2000s fades within ages. Thus, in the lack of political willingness to follow through on the IER’s recommendation to transform the site into a project for the preservation of memory, all those who have been in contact with the CDS-DMC from near or far refer to "blocked memory" (mémoire empêchée - Ricoeur, 2000, p. 83), preventing the work and duty of remembrance from being fully carried out.